Prevalence and risk factors of cholelithiasis in patients with spinal cord injury: A cross-sectional analysis - Rongfu Fan; Xinqi Cao; Zhihua Long; Bobo Ma; Qing Xu; Dejian Zhang (PLoS ONE, 2026)
Objective The purpose of the present study was to investigate the incidence of cholelithiasis and evaluate the risk factors for cholelithiasis in patients with spinal cord injury (SCI). Methods We analyzed 1,530 SCI patients (1,186 males and 344 females) from the China Rehabilitation Research Center (2010–2019) and compared patients with cholelithiasis (n = 289) and without cholelithiasis. The variables included age, gender, marital status, blood glucose level, motor function, and American Spinal Injury Association (ASIA) Impairment Scale (AIS) score. Results A total of 1530 patients with SCI, including 1186 males and 344 females, were included in this study. The prevalence of cholelithiasis was 18.89%. Univariate analysis revealed significant differences in age (P < 0.001), marital status (P < 0.001), blood glucose level (P < 0.001), and preserved motor function (P = 0.033). Multivariate analysis revealed the following independent risk factors: age ≥ 50 years (OR=1.637; 95% CI = 1.016–2.639; P = 0.043), being married (OR=1.902; 95% CI = 1.061–3.411; P = 0.031), lack of motor function (OR=1.587; 95% CI = 1.194–2.111; P < 0.001), and hyperglycemia (OR=1.764; 95% CI = 1.164–2.673; P = 0.007). Gender, lipid levels, SCI segment, and AIS grade were not significantly different. Conclusion Patients with SCI have a higher incidence of gallstones. Multivariate logistic regression analysis revealed that the occurrence of cholelithiasis in patients with SCI is closely related to age, marital status, blood glucose level and motor function preservation. Tailored preventive and therapeutic approaches should be developed for SCI patients, with intensified monitoring and intervention for high-risk patients to significantly improve quality of life.